Kritik Sosial Kebijakan Pemerintah dalam Platform Media Sosial dengan Pendekatan Komunikasi Hyperpersonal - Ichsan Muhammad Abduh; Hafied Cangara (Universitas Merdeka Malang, 2022)
Social media as a forum for communication and information, has a major contribution in its role in distributing and or transmitting information related to news related to social phenomena, one of which is government policies. Due to its nature as a communication medium, it creates space for the public to comment and express their aspirations on issues related to certain policies. This writing aims to describe the phenomenon of social criticism on social media platforms in the perspective of hyperpersonal communication. The advantage of hyperpersonal communication is how to deliver messages without being bound by space and time, causing an opportunity to plan the message to be conveyed. With this advantage, users can be wiser in using social media, choosing the right channel, and time to compose and distribute message content before deciding to respond to social issues or problems resulting from government policies.Keywords : Social Criticism, Policy, Social Media, Hyperpersonal Communication